Exploring the role of human resource management practices on labour productivity in Libyan national oil corporations - Mohamed M.I.; Mutalib M.A.; Abdulaziz A.M.; Ibrahim M. (Universiti Putra Malaysia, 2024)
Indexed by WOS/ Scopus